Certificação internacional de uma escola bicultural: circulação de práticas e saberes - Faricelli, Marilu de Freitas (2022)
This study addresses the certification of Colégio Humboldt, bilingual German Brazilian school as a "German international school of excellence". The objective is to demonstrate that, despite certification being part of the current model of educational homogenization, practices of the analyzed school reveal the genesis of a complex school culture. Such complexity is the result of the interaction among German Government's demands to spread its culture, Brazilian curricular requirements and teachers´ knowledge, whose daily practice intertwine various references, whether local, national or international. Analysis of teachers´ continuing education characteristics to adapt their didactic performance to the standards required by the certification reveal the circulation of ideas and practices, as well as evidence of shock between the German and Brazilian institutions. Reflections on educational practices in History classes, which brought together objectives, contents, methods and assessment of both school traditions, give birth to a new knowledge, as result of the pedagogical dialogue carried out between teachers from both countries and students´ learning needs. The analysis of official German documents of the certification process and of didactic material produced by teachers sought to relate what Dario Ragazzini conceived as layers of a document, which involve both the universe of the author(s), its production, use and circulation, such as the dialogue established between the researcher's questions and information contained in the source itself. Michel de Certeau's analysis of cultural practices was essential in developing the present thesis. Theoretical contributions of Agustin Escolano Benito were fundamental in the analysis of school practices